Incidence and Risk Factors for Radiotherapy-Induced Oral Mucositis Among Patients With Nasopharyngeal Carcinoma: A Meta-Analysis - Juejin Li; Chuanmei Zhu; Yun Zhang; Chang Guan; Qi Wang; Yuxin Ding; Xiaolin Hu (Elsevier, 2023)
SUMMARY: Purpose: To evaluate the incidence and identify the risk factors for radiotherapy-induced oral mucositis among patients with nasopharyngeal carcinoma. Methods: A meta-analysis was conducted. Eight electronic databases (Medline, Embase, Cochrane Library, CINAHL Plus with Full Text, Web of Science, China National Knowledge Infrastructure, Wanfang Database, and Chinese Scientific Journals Database) were systematically searched from inception to 4 March 2023 for relevant studies. Study selection and data extraction were conducted by two independent authors. The Newcastle‒Ottawa scale was used for quality assessment among the included studies. Data synthesis and analyses were performed in R software package version 4.1.3 and Review Manager Software 5.4. The pooled incidence was calculated using proportions with 95% confidence intervals (CIs), and the risk factors were evaluated using the odds ratio (OR) with 95% CIs. Sensitivity analysis and predesigned subgroup analyses were also conducted. Results: A total of 22 studies published from 2005 to 2023 were included. The results of the meta-analysis showed that the incidence of radiotherapy-induced oral mucositis was 99.0% among nasopharyngeal carcinoma patients, and the incidence of severe radiotherapy-induced oral mucositis was 52.0%. Poor oral hygiene, overweight before radiotherapy, oral pH < 7.0, the use of oral mucosal protective agents, smoking, drinking, combined chemotherapy, and the use of antibiotics at early treatment stage are risk factors for severe radiotherapy-induced oral mucositis. Sensitivity analysis and subgroup analyses also revealed that our results are stable and reliable. Conclusions: Almost all patients with nasopharyngeal carcinoma have suffered from radiotherapy-induced oral mucositis, and more than half of patients have experienced severe oral mucositis. Facilitating oral health might be the key focus of reducing the incidence and severity of radiotherapy-induced oral mucositis among nasopharyngeal carcinoma patients. Registration number: CRD42022322035.